Social and Gender Issues Related to the Implementation of the Traffic Discipline Zone (TDZ) in Malate, Manila - Era, Marlon (Animo Repository, 2023)
The worsening state of local traffic conditions in many cities has motivated local government units to implement new mechanisms that can improve the welfare of various stakeholders. The introduction of a traffic discipline zone (TDZ) is one of the recent innovations in managing road traffic. This study identifies the social and gender issues arising from the implementation of a TDZ through the conduct of focus group discussions. A diverse group of participants, including informal public utility drivers, ambulant vendors, barangay executives, and school officials, identified traffic and safety concerns in the vicinity of De La Salle University, Malate District in Manila, Philippines. A questionnaire survey was also conducted to supplement the results of the focus group discussions. These issues include the unavailability of parking spaces due to the increasing volume of vehicles; traffic violations of informal drivers such as tricycles and rickshaws, commonly known as pedicabs; and the proliferation of street vendors occupying the sidewalks. Furthermore, this study provides details regarding social issues, including the issue of gender in relation to pedicab drivers and vendors, such as pedicab drivers being male- dominated and female vendors being older and with more years of experience selling in the streets but earning less compared to male vendors. Recommendations on how to address these issues from the perspectives of the stakeholders are also discussed.